Veliparib Monotherapy to Patients With BRCA Germ Line Mutation and Platinum-Resistant or Partially Platinum-Sensitive Relapse of Epithelial Ovarian Cancer: A Phase I/II Study. Issue 9 (November 2017) - Steffensen, Karina Dahl; Adimi, Parvin; Jakobsen, Anders
Abstract : Objective: A new treatment principle, which seems to radically change the treatment approach in ovarian cancer (OC), has developed over the past few years. Poly(ADP-ribose) polymerase inhibitors work by interfering with mechanisms important to DNA damage repair. Cancer cells that already have defects in the BRCA genes are particularly sensitive to treatment with poly(ADP-ribose) polymerase inhibitors. The main purpose of this study was to investigate the effect of veliparib in patients with known BRCA1/2 mutations and with a platinum-resistant or intermediate sensitive relapse of OC. Methods: Major eligibility criteria were primary epithelial ovarian/fallopian/peritoneal cancer patients with a platinum-resistant or intermediate sensitive relapse of OC and with evaluable disease by either Response Evaluation Criteria In Solid Tumors or Gynecological Cancer Intergroup CA-125 criteria. Patients were treated with oral veliparib twice daily on days 1 to 28. Results: Sixteen patients were enrolled in the phase I part, and a maximum tolerable dose of 300 mg twice daily was established. The phase II part enrolled 32 patients with a median of 4 previous treatment regimens. The overall response rate combining Response Evaluation Criteria In Solid Tumors and CA-125 response was 65% (6% complete response and 59% partial response). Progression-free and overall survival rates of the intention-to-treat population were 5.6 months (95% confidence interval, 5.2–7.3 months) and 13.7 months (95% confidence interval, 10.2–17.3 months), respectively. The most common phase II treatment-related grade 2 toxicities included fatigue (22%), nausea (22%), and vomiting (9%). Conclusions: Treatment with veliparib in heavily pretreated patients with relapse of OC demonstrates a considerable efficacy with an acceptable toxicity profile.